NICOLAE ESINENCU – POETUL MODERN - MUNTEAN, LIUBA (BIBLIOPOLIS, 2020)
The poetical work of Nicolae Esinencu is the product of modern literary position. With an unprecedented fragmentary vision of the world, Nicolae Esinencu was and remained an emblem of uncomfortable and maverick writer who is always on strike against the society, in direct opposition to power, in fighting against the prejudices. For Nicolae Esinencu never existed „forbidden” topics and issues, formulas or expressions taboo. We intend to show the modernity of the work of Nicolae Esinenecu according to the principles of Hugo Friedrich (theorist of modernism) - ontological vision, his relationship with divinity which is a complicated one; language crisis, new words reinventing; complexity of lyrical ego and relationship with himself.